2017
DOI: 10.1021/acs.jnatprod.7b00668
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Icacinol from Icacina trichantha on Seedling Growth of Oryza sativa and Arabidopsis thaliana

Abstract: Broadleaf weeds are very costly for crop growers. Additional herbicidal compounds need to be obtained, especially from natural sources. Extracts of Icacina trichantha were evaluated for responses in germinating seeds and seedlings of rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana). An ethyl acetate fraction of I. trichantha tuber and a diterpenoid constituent, icacinol (1), were found to have impacts on germination and growth of seedlings. The seed germination inhibitory activity on rice was minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Apart from the momilactones, icacinol ( 24 ) caused significant damages to Arabidopsis leaf expansion. 44 Arabidopsis plant treated with 24 also showed indications of stress, where anthocyanins increased and chlorophyll was reduced. Such findings reinforce the hypothesis that (9 β- H)-pimarane lactones may serve as a potential source of agrichemicals.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from the momilactones, icacinol ( 24 ) caused significant damages to Arabidopsis leaf expansion. 44 Arabidopsis plant treated with 24 also showed indications of stress, where anthocyanins increased and chlorophyll was reduced. Such findings reinforce the hypothesis that (9 β- H)-pimarane lactones may serve as a potential source of agrichemicals.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…35 Phytochemical investigations of this plant in our laboratories have resulted in the isolation of 25 (9β-H)pimaranes and derivatives, including humirianthenolide C (11), 2β-hydroxyhumirianthenolide C (12), humirianthol (16), 14αmethoxyhumirianthol (18), icacinol (24), 17-hydroxyicacinol (25), icacenone (26), 7α-hydroxyicacenone (27), icacinlactones A−L (28, 30, 31, 34−42), 12-hydroxyicacinlactone A (29), 7αhydroxyicacinlactone B (32), 7β-hydroxyicacinlactone B (33), icacintrichanone (43), and icacintrichantholide (44). 29,36−39 The absolute configurations of 18, 27, 30, 31, 40, and 41 were established as (3S,4R,5R,6S,9S,10S,13S,14S,15S) (18), (2S,3R, 4R,5R,6S,7S,8S,9R) (27), (3S,4R,5R,6R,10R) (30), (2S,3R,4R, 5R,6R,10R) (31), and (3S,4R,5R,6R,8R,9R,10S) (40), (3S,4R, 5R,6R,10R) (41), and (3S,4R,5R,6R,10R) (44), respectively, by the single-crystal X-ray diffraction data. Compounds 28− 35, and 41−44 are proposed to be biosynthesized via a (9β-H)-pimarane pathway.…”
Section: Natural Distribution and Chemicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Their phytotoxic effects on the growth of the roots and shoots of several different seedlings were tested. Previous studies showed that pimarane and ent -pimarane diterpenoids both exhibited significant phytotoxic activities. However, few reports have examined the phytotoxic activities of ent -isopimarane diterpenoids. In the present study, some ent -isopimarane diterpenoids inhibited the growth of the roots and shoots of P. annua and Festuca arundinacea seedlings with inhibitory rates ranging from 50% to 84%.…”
mentioning
confidence: 99%